Ultrasound Stimulation Modulates Voltage-Gated Potassium Currents Associated With Action Potential Shape in Hippocampal CA1 Pyramidal Neurons - Lin, Zhengrong; Huang, Xiaowei; Zhou, Wei; Zhang, Wenjun; Liu, Yingzhe; Bian, Tianyuan; Niu, Lili; Meng, Long; Guo, Yanwu (Frontiers in Pharmacology, 2019)
Potassium channels (K+) play an important role in the regulation of cellular signaling. Dysfunction of potassium channels is associated with several severe ion channels diseases, such as long QT syndrome, episodic ataxia and epilepsy. Ultrasound stimulation has proven to be an effective non-invasive tool for the modulation of ion channels and neural activity. In this study, we demonstrate that ultrasound stimulation enables to modulate the potassium currents and has an impact on the shape modulation of action potentials (AP) in the hippocampal pyramidal neurons using whole-cell patch-clamp recordings in vitro. The results show that outward potassium currents in neurons increase significantly, approximately 13%, in response to 30 s ultrasound stimulation. Simultaneously, the increasing outward potassium currents directly decrease the resting membrane potential (RMP) from −64.67 ± 1.10 mV to −67.51 ± 1.35 mV. Moreover, the threshold current and AP fall rate increase while the reduction of AP half-width and after-hyperpolarization peak time is detected. During ultrasound stimulation, reduction of the membrane input resistance of pyramidal neurons can be found and shorter membrane time constant is achieved. Additionally, we verify that the regulation of potassium currents and shape of action potential is mainly due to the mechanical effects induced by ultrasound. Therefore, ultrasound stimulation may offer an alternative tool to treat some ion channels diseases related to potassium channels.